2022
DOI: 10.3889/oamjms.2022.8460
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Podoplanin in Hepatocellular Carcinoma in a Sample of Egyptian Population – Immunohistopathological Study

Abstract: BACKGROUND: Hepatocellular carcinoma (HCC) is a highly incident malignancy with a dreadful prognosis. It evolves through a multistep process, with a contribution from different stromal cells like cancer associated fibroblasts. Podoplanin is a glycoprotein that influences epithelial mesenchymal interplay facilitating the tumor invasion. AIM: The aim of the study was to evaluate the immunohistochemical expression of Podoplanin in HCC in cancer associated fibroblasts (CAFs) and malignant hepatocytes as well as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 53 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Researchers have suggested that testing for TFE3 rearrangement through immunostaining may be useful in the differential diagnosis of HEHE. Other markers such as ERG and AE1/AE3 are expressed in HEHE cells but are also expressed in other tumor cells and are therefore not useful for differential diagnosis [17,18].…”
Section: Molecular Characterizationmentioning
confidence: 99%
“…Researchers have suggested that testing for TFE3 rearrangement through immunostaining may be useful in the differential diagnosis of HEHE. Other markers such as ERG and AE1/AE3 are expressed in HEHE cells but are also expressed in other tumor cells and are therefore not useful for differential diagnosis [17,18].…”
Section: Molecular Characterizationmentioning
confidence: 99%